Pharmacokinetics of a New Immediate-release Compound Omeprazole Capsule and its Comparison with the Enteric-coated Formulation under Fasting and Fed Conditions - Liu, Z.; Ding, L.; Zhong, S.; Cao, X.; Jiang, L.; Duan, H. (Drug Research, 2013)
The present study was conducted to describe the pharmacokinetic profile of immediate-release compound omeprazole capsule and compare it with the enteric-coated formulation under fasting and fed condition.This study was designed to phase I, open-label, randomized, 3-part clinical trial. 12 subjects in part one received single doses (20 mg and 40 mg) and repeated doses (20 mg). Different 30 subjects in part 2 (fasting condition) and part 3 (fed condition) received either compound omeprazole capsule (40 mg) or delayed-release omeprazole (40 mg) separated by 7 days.Compound omeprazole capsule showed dose non-proportionality in the range from 20 mg to 40 mg. The AUC0–t of 20 mg omeprazole is 78% higher after repeated doses. The Cmax was higher and Tmax was lower for compound omeprazole capsule than delayed-release omeprazole. 90% CIs for AUC0–t of the 2 periods (test/reference) under fasting and fed conditions were 106.3% (102.2%~109.2%) and 104.1% (93.4%~109.6%), respectively. Presence of food reduced the rate (Cmax) and extent (AUC0–t) of systemic exposure of the test and reference formulations from 1 462 to 777 ng · mL−1, 1 055 to 602 ng · mL−1, 2 597 to 1 852 ng · h · mL−1 and 2 454 to 1 873 ng · h · mL−1, respectively.Exposed dose of omeprazole in subjects with compound omeprazole capsule was time- and dose-dependent. Compared with delayed-release omeprazole, compound omeprazole capsule had rapid but similar degree of absorption of omeprazole.
Keywords: pharmacokinetics; omeprazole; non-proportionality; CYP2C19; food